2018
DOI: 10.15171/ijhpm.2018.32
|View full text |Cite
|
Sign up to set email alerts
|

The International Landscape of Medical Licensing Examinations: A Typology Derived From a Systematic Review

Abstract: Background: National licensing examinations (NLEs) are large-scale examinations usually taken by medical doctors close to the point of graduation from medical school. Where NLEs are used, success is usually required to obtain a license for full practice. Approaches to national licensing, and the evidence that supports their use, varies significantly across the globe. This paper aims to develop a typology of NLEs, based on candidacy, to explore the implications of different examination types for workforce plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 55 publications
0
38
0
3
Order By: Relevance
“…Competing demands of internal and external stakeholders may raise tensions between equivalency (such as through the implementation of national licensing tests) and alignment with the medical school's or workplace curriculum. Serious dilemmas may then arise in contexts in which efforts to ensure quality of assessment for accountability through top‐down, prescriptive (national) mandates or tests are interpreted to signify loss of programme autonomy and professional integrity, whereas non‐compliance may result in the loss of programme accreditation …”
Section: Polarities and Tensions In Assessment: Categorisation And Dementioning
confidence: 99%
See 1 more Smart Citation
“…Competing demands of internal and external stakeholders may raise tensions between equivalency (such as through the implementation of national licensing tests) and alignment with the medical school's or workplace curriculum. Serious dilemmas may then arise in contexts in which efforts to ensure quality of assessment for accountability through top‐down, prescriptive (national) mandates or tests are interpreted to signify loss of programme autonomy and professional integrity, whereas non‐compliance may result in the loss of programme accreditation …”
Section: Polarities and Tensions In Assessment: Categorisation And Dementioning
confidence: 99%
“…Serious dilemmas may then arise in contexts in which efforts to ensure quality of assessment for accountability through top-down, prescriptive (national) mandates or tests are interpreted to signify loss of programme autonomy and professional integrity, whereas non-compliance may result in the loss of programme accreditation. 52,53 Obviously, well-described and well-researched tensions between assessment design and assessment for and of learning reflect competing demands of reliability, validity, feasibility and acceptance. These tensions surface in debates around qualitative versus quantitative assessment approaches, 26 the role of 'objectification' (objectivity) versus subjectivity 54,55 and a psychometric versus 'edumetric' or educational approach to assessment design.…”
Section: Polarities and Tensions In Assessment: Categorisation And Dementioning
confidence: 99%
“…It has been opined by academics, practitioners, laypersons, students, and others that QEs are necessary for a variety of reasons, but most reasons relate to the importance of QEs to society. [2][3][4]11 Price and colleagues 12 presented a typology of QEs based on an exhaustive review of international requirements for medical licensure. They suggested that there are 4 options for licensure based on candidacy.…”
Section: Introductionmentioning
confidence: 99%
“…Da mesma forma, a experiência vivenciada com a eficácia dos ELMs em garantir domínio minimamente satisfatório de conhecimentos e habilidades para o exercício da Medicina faz países como Alemanha, Bahrein, Canadá, Chile, Coréia do Sul, Croácia, Emirados Árabes, EUA, França, Hong Kong, Japão, Polônia e Catar manter os seus exames 13 , que, nos EUA e no Canadá, têm tradição de execução de mais de 100 anos e vêm ainda sendo aperfeiçoados periodicamente 14 .…”
unclassified
“…É cabível considerar que a introdução de ELM possa trazer consequências deletérias para a qualidade da formação médica, o que será inevitável se essa medida for configurada por exame único pontual de conhecimentos. Por isso, os ELMs dos EUA e do Canadá abrangem também as habilidades clínicas, avaliadas com exames objetivos e estruturados 13 . As provas de conhecimentos básicos e clínicos podem ser cumpridas pelo estudante ou médico já graduado em momentos diversos, ao longo de anos, enquanto a etapa final -de exame estruturado de competências clínicas com pacientes simulados -deve ser cumprida após a aprovação nas etapas anteriores 13 .…”
unclassified